Superabsorbent Polymer Based on Sodium Carboxymethyl Cellulose Grafted Polyacrylic Acid by Inverse Suspension Polymerization - Pairote Klinpituksa; Patchareeya Kosaiyakanon (International Journal of Polymer Science)
A superabsorbent polymer (SAP) based on graft copolymerization of sodium carboxymethyl cellulose and acrylic acid was prepared by inverse suspension polymerization using potassium persulfate as an initiator and N,N′-methylenebisacrylamide as a cross-linker. Experiments were performed at 70°C for 90 min but varying the concentrations of sodium carboxymethyl cellulose (NaCMC), acrylic acid (AA), potassium persulfate (KPS), and N,N′-methylenebisacrylamide (MBA), and also varying % neutralization of AA. The maximum swelling capacity for SAP was 544.95 g/g in distilled water and 44.0 g/g in 0.9% w/v NaCl solution. This near optimal SAP was prepared using 2.0 g/100 mL NaCMC, 1.0 mol/L AA with 70% neutralization, 0.014 mol/L KPS, and 0.01 mol/L MBA.